A simple mathematical model of rhegmatogenous retinal detachment. (October 2018) - Natali, Damiano; Repetto, Rodolfo; Tweedy, Jennifer H.; Williamson, Tom H.; Pralits, Jan O.
Abstract: The conditions under which rhegmatogenous retinal detachment occurs are poorly understood, which hampers the success rates of surgery. Fluid dynamical effects play a major role, and in this paper we analyse the tendency for the retina to detach further in both the case of a free flap giant retinal tear (GRT) and in the case of a retinal hole (RH). For this purpose we use a mathematical model to investigate the interaction between the fluid flow and the detached retina during saccadic eye movements. The governing equations are solved numerically using a code developed ad hoc. An idealised two-dimensional geometry is used and realistic values of almost all governing parameters are taken from the literature. For the cases of both GRT and a RH we investigate the tendency for the detachment to progress, analysing two different saccadic motions, different lengths of the detached retina, different attachment angles and, in the case of a RH, different hole diameters. In both cases we find that increasing the length of the detached retina increases the tendency for further detachment, while in the RH case, changing its diameter has little or no effect. We also find the existence of an attachment angle that maximises the tendency to detach, and the model indicates that RHs are more prone to detach further than GRTs. In spite of the fact that the model is highly idealised the results agree qualitatively well with the available clinical evidence.